Вenzimidazole derivatives with anticonvulsant activity and their pharmacological targets - A. D. Matveev; A. M. Shirshina; G. V. Pridvorov; O. Yu. Mukha (Сибирский научный медицинский журнал)
Key biomolecular targets involved in regulating neuronal excitability are discussed, and recent findings on benzimidazole derivatives exhibiting anticonvulsant activity are presented. The relationship between their structure and anticonvulsant activity is closely analyzed. The literature review revealed that benzimidazoles possess diverse biological activities and significant potential for modulating ion channels, receptors, and other targets implicated in epileptogenesis, making them a promising scaffold for the development of novel antiepileptic drugs; can enhance GABAergic neurotransmission,showing strong anticonvulsant properties in various experimental models of epilepsy; antagonize NMDA receptors, which helps reduce neuronal hyperexcitability and provides neuroprotective effects; modulate T-type calcium channels and TRPM7 channels, which are important targets for treating absence epilepsy and preventing relapses of status epilepticus. Selective kappa opioid receptor agonists also demonstrate anticonvulsant effects and the ability to block excitotoxicity. Ligands that act on peroxisome proliferator-activated receptors gamma, KV7 channels, and purine P2X3 receptors are also considered. Continued research in this field may lead to the discovery of effective and well-tolerated medications for managing epilepsy.